Interventions to Address Clinical Incivility in Nursing: A Systematic Review. - Lama, Anne; Nwamu, Henrietta; Kim, Younglee (Nursing Reports, 2025)
Background/Objectives: Clinical incivility is a persistent issue in nursing education and practice, with negative impacts on students, educators, and clinicians. Uncivil behaviors—such as belittling, exclusion, and dismissiveness—compromise communication, teamwork, and patient safety. Although various interventions have been implemented, their effectiveness remains inconsistent. This systematic review aimed to evaluate the effectiveness of interventions addressing clinical incivility in nursing and to identify common trends, gaps, and implications for future practice and research. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted in PubMed, Web of Science, and EBSCOhost (CINAHL) for peer-reviewed empirical studies published between 2014 and 2024. Search terms included "clinical incivility" and ("intervention" or "program" or "training") and "nursing". Studies were eligible if they evaluated interventions aimed at reducing incivility among nursing students, faculty, or practicing nurses. Seventeen studies met the inclusion criteria and were analyzed for intervention types, target populations, delivery methods, and outcomes. Results: The review identified five main intervention types: educational modules (n = 9), cognitive rehearsal (n = 5), simulation and role-play (n = 5), team-based strategies (n = 3), and feedback/communication strategies (n = 2). Many studies used multiple strategies. Fourteen studies reported positive outcomes such as improved awareness, communication, and self-efficacy. Eight studies demonstrated statistically significant reductions in perceived incivility, particularly those with simulation-based, multi-session, or institutionally supported formats. Three studies showed limited or mixed results due to insufficient follow-up or lack of leadership engagement. Conclusions: Experiential and multi-component interventions appear effective in reducing clinical incivility. Long-term success requires leadership engagement, institutional support, and integration into ongoing professional development.